2016
DOI: 10.3390/biology5040049
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase-1 Regulates Expression of Neuregulin-1

Abstract: Protein phosphatase 1 (PP1), a cellular serine/threonine phosphatase, is targeted to cellular promoters by its major regulatory subunits, PP1 nuclear targeting subunit, nuclear inhibitor of PP1 (NIPP1) and RepoMan. PP1 is also targeted to RNA polymerase II (RNAPII) by NIPP1 where it can dephosphorylate RNAPII and cycle-dependent kinase 9 (CDK9). Here, we show that treatment of cells with a small molecule activator of PP1 increases the abundance of a neuregulin-1 (NRG-1)-derived peptide. NRG-1 mRNA and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…NIPP1 can also activate transcription as it induces expression of mesenchymal genes in HeLa cells [41]. We recently reported that NIPP1 represses expression of neuregulin-1, a heparin-binding neurotrophic factor [42]. Thus, deregulation of PP1 can enhance transcription of normally repressed genes, including integrated HIV-1 provirus.…”
Section: Regulation Of Hiv-1 Transcription By Protein Phosphatase-1mentioning
confidence: 99%
“…NIPP1 can also activate transcription as it induces expression of mesenchymal genes in HeLa cells [41]. We recently reported that NIPP1 represses expression of neuregulin-1, a heparin-binding neurotrophic factor [42]. Thus, deregulation of PP1 can enhance transcription of normally repressed genes, including integrated HIV-1 provirus.…”
Section: Regulation Of Hiv-1 Transcription By Protein Phosphatase-1mentioning
confidence: 99%
“…In this work, we show that PP1c is recruited to promoters by RFX1. PP1c dephosphorylates and subsequently affect the function of transcription factor as well as components of the general transcription machinery [33][34][35][36][37][38][39]. We suggest a model for the context dependent function of RFX1 which is achieved by recruiting PP1c to promoters leading to the de-phosphorylation of neighboring factors.…”
Section: Introductionmentioning
confidence: 99%